2018
DOI: 10.1590/1516-4446-2017-2449
|View full text |Cite
|
Sign up to set email alerts
|

Pituitary gland volumes in patients with obsessive-compulsive disorder before and after cognitive-behavioral therapy

Abstract: Our results indicate an absence of post-CBT volumetric changes in the pituitary gland of OCD patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 22 publications
(23 reference statements)
0
2
0
Order By: Relevance
“…Recently, Atmaca et al (46), compared 12 OCD patients with12 HC using MRI, and found reduced pre-treatment pituitary gland volumes in the OCD group. No change in pituitary gland volume was detected after16-week CBT, suggesting that the clinical efficacy of CBT does not impact on this neural structure in OCD.…”
Section: Magnetic Resonance Imaging Studiesmentioning
confidence: 99%
“…Recently, Atmaca et al (46), compared 12 OCD patients with12 HC using MRI, and found reduced pre-treatment pituitary gland volumes in the OCD group. No change in pituitary gland volume was detected after16-week CBT, suggesting that the clinical efficacy of CBT does not impact on this neural structure in OCD.…”
Section: Magnetic Resonance Imaging Studiesmentioning
confidence: 99%
“…Brain function in OCD has been investigated using functional magnetic resonance imaging, structural brain morphology, positron emission tomography and EEG methods (Linden, 2006; O’Neill et al, 2013; Dohrmann et al, 2017; Moody et al, 2017; Atmaca et al, 2018). In particular, hyperactivity of the cortico-striato-thalamo-cortical (CSTC) circuit has been proposed as the neurobiological basis of OCD (Saxena et al, 2001).…”
Section: Introductionmentioning
confidence: 99%